Teacher Performance Based on The Visionary Leadership Style of School, Competency and Work Discipline (Study at Muhammadiyah Setiabudi Pamulang College) - Ading Sunarto; Asridah Warni Tanjung; Nindie Ellesia (Journal of Research in Business, Economics, and Education, 2020)
The purpose of holding this study was to determine and analyze the influence of the Principal's Visionary Leadership Style, Competence and Work Discipline on Teacher Performance at Muhammadiyah Setiabudi Pamulang. The method used in this research is descriptive method with a quantitative approach. The number of samples used in this study were 100 respondents using saturated sampling technique. The data analysis technique used in this research is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple linear regression, multiple linear regression, coefficient of determination, and F-test. The results of this study are as follows: Simultaneously the principal's visionary leadership style, competence, and work discipline have a positive and significant effect on Teacher Performance at Muhammadiyah Setiabudi Pamulang, this can be proven from the value of Fcount 36.276> Ftable 3.09 with a significant level of 0.000 <0.05, the amount of contribution Principal's visionary leadership style, competence, and work discipline simultaneously on Teacher Performance at Muhammadiyah Setiabudi Pamulang by 53.1%.